Apgar scores at 10 min and outcomes at 6–7 years following hypoxic-ischaemic encephalopathy. Issue 6 (29th July 2013) - Natarajan, Girija; Shankaran, Seetha; Laptook, Abbot R; Pappas, Athina; Bann, Carla M; McDonald, Scott A; Das, Abhik; Higgins, Rosemary D; Hintz, Susan R; Vohr, Betty R; ,
Abstract : Aim: To determine the association between 10 min Apgar scores and 6–7-year outcomes in children with perinatal hypoxic-ischaemic encephalopathy (HIE) enrolled in the National Institute of Child Health and Human Development Neonatal Research Network (NICHD NRN) whole body cooling randomised controlled trial (RCT). Methods: Evaluations at 6–7 years included the Wechsler Preschool and Primary Scale of Intelligence III or Wechsler Intelligence Scale for Children IV and Gross Motor Functional Classification Scale. Primary outcome was death/moderate or severe disability. Logistic regression was used to examine the association between 10 min Apgar scores and outcomes after adjusting for birth weight, gestational age, gender, outborn status, hypothermia treatment and centre. Results: In the study cohort (n=174), 64/85 (75%) of those with 10 min Apgar score of 0–3 had death/disability compared with 40/89 (45%) of those with scores >3. Each point increase in 10 min Apgar scores was associated with a significantly lower adjusted risk of death/disability, death, death/IQ <70, death/cerebral palsy (CP) and disability, IQ<70 and CP among survivors (all p<0.05). Among the 24 children with a 10 min Apgar score of 0, five (20.8%) survived without disability. The risk-adjusted probabilities of death/disability were significantly lower in cooled infants with Apgar scores of 0–3; there was no significant interaction between cooling and Apgar scores (p=0.26). Conclusions: Among children with perinatal HIE enrolled in the NICHD cooling RCT, 10 min Apgar scores were significantly associated with school-age outcomes. A fifth of infants with 10 min Apgar score of 0 survived without disability to school age, suggesting the need for caution in limiting resuscitation to a specified duration.